Characterizing viral exanthems. Issue 6 (December 2010) - Lam, Joseph M
An exanthem is any eruptive skin rash that may be associated with fever or other systemic symptoms. Causes include infectious pathogens, medication reactions and, occasionally, a combination of both. In children, exanthems are most often related to infection and, of these, viral infections are the most common. Some exanthems have very specific morphologies that help identify and characterize the eruption. In this article, we describe common and uncommon viral exanthems, based on their morphology, and review current advancements in understanding and treatment of these exanthems.